Gaming in the Irish single electricity market and potential effects on wholesale prices - Darragh Walsh; Laura Malaguzzi Valeri (The Economic and Social Research Institute (ESRI), 2014)
The Irish Single Electricity Market is establishing how to comply with the European Union Target Model. One option is to move away from the regulated environment used in the current design and allow generating firms to bid freely in the market. This study shows that in 2011, allowing firms to freely compete in quantities (Cournot) would have increased prices by 52%, using Irish-specific estimates for the price elasticity of demand. When redesigning the market, regulators should consider how best to control market power.
Keywords: 330